Linkage to care and antiretroviral therapy initiation by testing modality among individuals newly diagnosed with HIV in Tanzania, 2014–2017. Issue 12 (24th October 2018) - Rentsch, Christopher T.; Wringe, Alison; Machemba, Richard; Michael, Denna; Urassa, Mark; Todd, Jim; Reniers, Georges; Zaba, Basia
Abstract: Objective: To measure linkage to care and antiretroviral therapy (ART) initiation among newly diagnosed individuals with HIV in a rural Tanzanian community. Methods: We included all new HIV diagnoses of adults made between 2014 and 2017 during community‐ or facility‐based HIV testing and counselling (HTC) in a rural ward in northwest Tanzania. Community‐based HTC included population‐level HIV serological testing (sero‐survey), and facility‐based HTC included a stationary, voluntary HTC clinic (VCT) and an antenatal clinic (ANC) offering provider‐initiated HTC (ANC‐PITC). Cox regression models were used to compare linkage to care rates by testing modality and identify associated factors. Among those in care, we compared initial CD4 cell counts and ART initiation rates by testing modality. Results: A total of 411 adults were newly diagnosed, of whom 10% (27/265 sero‐survey), 18% (3/14 facility‐based ANC‐PITC) and 53% (68/129 facility‐based VCT) linked to care within 90 days. Individuals diagnosed using facility‐based VCT were seven times (95% CI: 4.5–11.0) more likely to link to care than those diagnosed in the sero‐survey. We found no difference in linkage rates between those diagnosed using facility‐based ANC‐PITC and sero‐survey ( P = 0.26). Among individuals in care, 63% of those in the sero‐survey had an initial CD4 count >350 cells/mm 3 vs . 29% of those using facility‐based VCT ( P = 0.02). The proportion who initiated ART within 1 year of linkage to care was similar for both groups (94% sero‐survey vs . 85% facility‐based VCT; P = 0.16). Conclusions: Community‐based sero‐surveys are important for earlier diagnosis of HIV‐positive individuals; however, interventions are essential to facilitate linkage to care.